2017
DOI: 10.1016/j.joca.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of undenatured native chicken type II collagen (UC-II) diminished deterioration of articular cartilage in a rat model of osteoarthritis (OA)

Abstract: Study results demonstrate that a clinically relevant daily dose of UC-II when applied immediately after injury can improve the mechanical function of the injured knee and prevent excessive deterioration of articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
69
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 45 publications
5
69
1
9
Order By: Relevance
“…Even at the smaller dosages, UC-II has also been reported to be more effective than the glucosamine and chondroitin sulfate supplements, which are the supplements most frequently used in the market. In this review, we summarize the effects of UC-II on joint health and function in health and disease conditions in companion animals.Animals 2020, 10, 697 2 of 24 run, articular cartilage degeneration results in changes to both as metabolisms of chondrocytes and synoviocytes such that inflammatory cytokines that are formed damage the ability of chondrocytes to renovate the cartilage matrix [8,13,17].The main goal in OA management in animals is to control clinical findings by protecting the joints from OA, reducing pain, increasing mobility, and, therefore, the quality of life [18]. For this purpose, non-pharmaceutical treatment options include surgery, weight loss, exercise modification, and physical therapy [19].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Even at the smaller dosages, UC-II has also been reported to be more effective than the glucosamine and chondroitin sulfate supplements, which are the supplements most frequently used in the market. In this review, we summarize the effects of UC-II on joint health and function in health and disease conditions in companion animals.Animals 2020, 10, 697 2 of 24 run, articular cartilage degeneration results in changes to both as metabolisms of chondrocytes and synoviocytes such that inflammatory cytokines that are formed damage the ability of chondrocytes to renovate the cartilage matrix [8,13,17].The main goal in OA management in animals is to control clinical findings by protecting the joints from OA, reducing pain, increasing mobility, and, therefore, the quality of life [18]. For this purpose, non-pharmaceutical treatment options include surgery, weight loss, exercise modification, and physical therapy [19].…”
mentioning
confidence: 99%
“…There are also pharmaceutical treatment options. For example, glucosamine, chondroitin, undenatured form of type II collagen, pentosane polysulphate, avocado/soybean unsaponifiables, green-lipped mussel, milk protein, creatine, and amino acid represent the largest category of natural supplements for veterinary medicine [16].The undenatured form of type II collagen (UC-II), a nutritional supplement, is derived from chicken sternum cartilage and is a powdered, glycosylated, and shelf-resistant component [17]. Previous studies have revealed that UC-II reduced lameness after general pain, pain during limb manipulation, and physical exertion in arthritic dogs given 4 mg or 40 mg of UC-II daily [20].…”
mentioning
confidence: 99%
See 3 more Smart Citations